How and When are We Right to Prioritize the Interests of Residents and Citizens?. (March 2020) - Camacho Beltrán, Enrique
This article assesses an assumption pervasive in one strain of arguments in favor of stringent immigration controls. The assumption affirms that—for the case of regular admissions—to a certain extent states are permitted to prioritize the interests of their citizens and residents by issuing exclusionary immigration policies (call this the priority assumption). Using the normative methodology of applied international ethics, I suggest some broad constraints to this priority assumption that have a bearing on justifications for current practical immigration policy in Europe, North America, and beyond. I do so by redefining borders as domestic-international institutions that open up borders not only to (internal) standards of justice but also to standards of international legitimacy.